Natural resource use as a coping and adaptation strategy to floods of vulnerable populations in the Eastern Cape - Sachikonye, Mwazvita Tapiwa Beatrice (Rhodes University, Faculty of Science, Department of Environmental Science, 2015)
Many of the anticipated increased occurances of natural hazards are not only a consequence of climate change, but rather of rapid and widespread land cover change and the subsequent loss of the buffering capacity provided by healthy ecosystems against natural hazards. Unplanned and unmanaged developments in informal settlements limit government's ability to mitigate and manage, pointing towards natural resources as being integral for vulnerable communities in developing countries to cope with and mitigate flood disasters. There is a lack of understanding on how natural resources contribute to resilience of vulnerable populations in the Eastern Cape and how they are impacted by these populations before, during and after a flood shock. There also exists a gap in knowledge on how natural resources can mitigate the physical impacts of flooding in South Africa, more so in the Eastern Cape province. Using household questionnaires and GIS techniques, the strategies that households used to recover from the October 2012-February 2013 flood shocks were investigated in informal settlements of three towns (Grahamstown, Port Alfred and Port St Johns). Within the vulnerability paradigm and the sustainable livelihood framework, the study also quantified and evaluated the relative contribution of natural resources to recovery strategies, and lastly, the study investigated how patterns of land use, state of natural vegetation and household topographical location exacerbated or diminished the physical impacts of flooding. This study found that natural resources contributed up to 70 percent to recovery of households from the flood shock, most of this being to reconstruction of housing structures after the flood, less so to economic recovery. It was also found that at a settlement scale the buffering effect of vegetation, although variable amongst settlements, was significant. Settlements that were dominated by dense bush and small trees experienced up to 46 percent less impacts on their property than those surrounded by bare gravel and impervious roofs with degraded environments. The main findings of the research show that natural resources reduce the vulnerability of households in informal settlements to flooding in two significant ways; by physically mitigating against damage to shelters and by also providing an emergency-net function that substitutes financial capital in households. Their inclusion in disaster management has the potential to encourage the sustainable livelihoods of the urban poor in the Eastern Cape
Keywords: Flood damage prevention -- South Africa -- Eastern Cape; Natural resources -- South Africa -- Eastern Cape; Land use -- South Africa -- Eastern Cape; Human ecology -- South Africa -- Eastern Cape; Nature -- Effect of human beings on -- South Africa -- Eastern Cape; Human beings -- Effect of environment on -- South Africa -- Eastern Cape